Surveillance of healthcare-associated bloodstream infections in neonatal intensive care unit of a tertiary care hospital - Rakshit, Pue; Nagpal, Nitika; Banerjee, Tuhina; Kumar, Ashok (International Journal of Infection Control, 2026)
Background and objective: Healthcare-associated infections (HAIs) are a serious threat to patient safety. They cause substantial morbidity and mortality across various healthcare settings, including neonatal intensive care units (NICUs). This study was undertaken to determine the incidence of HA bloodstream infection (HA-BSI) in the NICU of a tertiary care hospital. Methodology: Data were collected in a systematic manner based on the Centers for Disease Control and Prevention (CDC) guidelines for the surveillance of HAI for a period of 1 year (Jan–Dec, 2022). The HAI rate was calculated using the following formula: No. of cases/No. of patient days × 1,000. Result: Among the 1,085 admitted neonates, the incidence of HA-BSI was 15.80/1,000 patient days. HAI was seen in neonates having mean birth weight 1,722.5 ± 113.906 g, mean gestational age 29.6 ± 1.38, and mean duration of hospital stay 13.8 ± 4.081 days. Among the 80 cases of HA-BSI, recognized pathogens were 22 (27.5%) Klebsiella pneumoniae, 16 (20%) non-albicans Candida, 13 (16.25%) methicillin-sensitive Staphylococcus aureus, 10 (12.5%) Candida albicans, 10 (12.5%) Acinetobacter baumannii, 4 coagulase-negative staphylococci, 3 (3.75%) methicillin-resistant Staphylococcus aureus, 1 (1.25%) Escherichia coli, and 1 (1.25%) Enterococcus. The mortality rate was 56.78%. Conclusion: The predominance of K. pneumoniae and A. baumannii as causative pathogens suggests the need of stringent infection control measures and targeted antimicrobial strategies to reduce the burden of HAI and improve patient outcomes.